Gogadget: An R Package for Interpretation and Visualization of GO Enrichment Results. Issue 5 (21st December 2016) - Nota, Benjamin
Abstract: Gene expression profiling followed by gene ontology (GO) term enrichment analysis can generate long lists of significant GO terms. To interpret these results and get biological insight in the data, filtering and rearranging these long lists of GO terms might be desirable. The R package gogadget provides functions to modify GO analysis results, with a simple filter strategy. Furthermore, it groups redundant GO terms with hierarchical clustering and presents the results in a colorful heatmap. The filtered GO term enrichment results can also be exported by the package for subsequent analysis in Cytoscape Enrichment Map. The R package is freely available under the terms of the GNU GPLv3 athttps://sourceforge.net/projects/gogadget/ . Abstract :